Call for regulation of social media health content: an initiative of the Italian Association of Hospital Dermatologists (ADOI) (Dermatology Reports, 2024)
Social media platforms have become an indispensable part of modern society, with approximately 59.9% of the global population actively engaging on these platforms. In the realm of healthcare, and particularly in dermatology, a specialty that relies heavily on visual assessment and patient education, social media serves as a powerful conduit for disseminating information. The ability to share visual content makes these platforms uniquely suited to raising awareness about skin health, promoting preventive measures, and encouraging early detection of dermatological conditions. [...]